The impact of mobile applications on medication adherence: a systematic review. Issue 6 (6th August 2019) - Ng, Ricki; Carter, Stephen R; El-Den, Sarira
Abstract : There is strong bi-partisan public support for evidence to have much more influence on health policy development in U.S. Congress. Abstract: In 2008, Apple and Android launched their Application or "App" stores. Since then, there has been a growing interest in using mobile apps for improving medication adherence. However, research on the efficacy of apps, in terms of improved medication adherence and clinical outcome and/or patient-related outcome measures (PROMs) is scarce. The objective of this research was to systematically review the impact of apps on consumers' medication adherence and to determine the effect on clinical outcome and/or PROM(s). A systematic literature search was conducted to identify publications aimed at improving medication adherence published from January 2008 to April 2018. All studies were assessed for risk of bias using either the Risk Of Bias In Non-randomized Studies-of Interventions or the revised tool for Risk of Bias in randomized trials tool, depending on study design. Eleven randomized controlled trials (RCTs) and 10 non-RCTs were included. All 11 RCTs showed improvements in adherence; however, only seven reported statistically significant improvements in at least one adherence measure. Nine RCTs also demonstrated improvements in clinical outcome/PROM(s), of which five were statistically significant, whereas two RCTs did not report on clinical outcome/PROM(s). Only two studies using non-RCT study designs showed statistically significant improvements in all measures of adherence and clinical outcome/PROM(s). The risk of bias was moderate or serious for all included studies. Even though the use of an app may improve adherence, it is difficult to draw conclusions regarding the impact of apps on medication adherence due to the high degree of heterogeneity across studies, from the methodological design to the features of the app and the measure of adherence.